Penentuan tarif sewa kamar kost melalui perhitungan harga pokok kamar menggunakan metode activity based costing (Studi kasus Eben Kost Manado) - Febrian, Reynal; Runtu, Treesje; Maradesa, Djeini (Yayasan Widyantara Nawasena Raharja, 2024)
Achieving maximum profit is closely tied to specific calculations regarding the costs incurred to produce a service product, such as the cost of a room. Activity-Based Costing (ABC) is one method used to calculate the cost of a room by evaluating expenses based on the resources consumed by various activities. The objective of this research is to determine room rental rates by calculating the cost of a room using the Activity-Based Costing method at Eben Kost Manado. The research employed a qualitative descriptive approach. Data collection techniques included interviews and documentation. The findings indicate that the room rental rates determined using the Activity-Based Costing method are lower compared to those set by Eben Kost because the ABC method allocates all activity costs to each room type precisely based on each activity's consumption.